2022
DOI: 10.1155/2022/8151161
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-29a-3p Regulates SH-SY5Y Cell Proliferation and Neurite Growth through Interaction with PTEN-PI3K/AKT/mTOR Signaling Pathway

Abstract: The effects of microRNA-29a-3p in the proliferation process of nerve cells are unclear. The purpose of this study is to delve into the regulatory role of microRNA-29a-3p, via interaction with phosphatase and tension homolog (PTEN), in the SH-SY5Y cell proliferation process. Different expressions of microRNA-29a-3p in the SH-SY5Y cells were constructed by transfected miRNA-29a-3p mimic and inhibitor. The effects of cell transfection and the mRNA expressions of PTEN, Akt, and mTOR were detected by qPCR. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…OD value at 570 nm was measured for enzyme-linked immunosorbent assay (ELISA). Cell viability was calculated according to the manufacturer's manual [7].…”
Section: Cellmentioning
confidence: 99%
“…OD value at 570 nm was measured for enzyme-linked immunosorbent assay (ELISA). Cell viability was calculated according to the manufacturer's manual [7].…”
Section: Cellmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%